Abertura comercial e inflação: uma evidência empírica para o Brasil - Macedo, Isac de Alcântara (2007)
This dissertacion analyzes the effect of the commercial opening, from the decade of ninety, on the tax of inflation in Brazil. In accordance with theoretical and empirical on this relation, how much bigger literature the commercial, lesser opening the impact of discretional monetary politics on the inflation tax. In this direction, using information of the Brazilian States, referring to the period between 1990 and 2003, esteem two econometrical models with data in panel with the objective to verify if the correlation enters the inflation tax and economic opening is negative. In accordance with Romer (1993), in economies with stability and independent Central banking this correlation would have to be weak or not significant. For the Brazilian case it is of if waiting that this relation if does not keep in function of the Real Plan, from 1994, for having stabilized the Brazilian economy and data bigger autonomy to the Central banking in the conduction of the monetary politics. Simultaneously, at the beginning of the decade of ninety, the economy intensified the process of the economic opening. In fact, the results gotten from the esteem of the models had shown that the impact of the opening on the inflation tax was not significant and that the determinative factors for its decline had been the effect of the Real Plan together with the biggest autonomy of the Central banking.